The impact of digital payments on the state of financial inclusion in the Philippines - Armedilla, John Isaac C. (Animo Repository, 2022)
Digital payments had steadily increased since the outbreak, when everyone was encouraged to use them. Unlike related studies, the researchers collected data from financial service users on both the supply and demand sides. This paper analyses financial inclusion in households that use financial services and the factors that impact access to financial inclusion. It quantifies the determinants affecting low-income groups' participation in formal financial markets and examines whether digital payment indicators influence financial inclusion in the Philippines or vice versa. The research examines digital payments and financial inclusion in the Philippines using a unique data set that mixes pooled cross-sectional data with household-level characteristics. First, only debit cards and remittances affect low-income bank account openings. Second, government cash transfers, not digital payments, enable low-income families to become financially included. Finally, digital payments help eliminate some financial inclusion barriers. This paper's empirical findings help create digital payment rules and regulations to improve financial inclusion for economic growth.